Three Essays on the Economics of Immigration - Tu, Jiong (My University, 2010)
The three essays in this thesis conduct empirical research on the economics of immigration using data from the Canadian Censuses. In the first paper, I analyze the impact of immigration on native-born Canadians' wage growth by combining an area approach and a skill approach. The estimated effects of immigration from both a first difference regression and a two-stage regression are either statistically insignificant or significantly positive. The results indicate that there is no evidence for a negative impact of the large immigrant influx during the 1990s on the wage growth of natives. The second essay examines the impact of residence in an ethnic enclave on male immigrants' labour force activities. For recent immigrants who arrived in Canada within ten years, the intensity of enclave residence is found to be negatively associated with their labour force participation rate, but positively correlated with their employment probability. However, living in an enclave has no significant effect on the labour force activity of old immigrants whose years-since-migration is more than twenty. These findings are robust to probit and instrumental variable estimations. In the third essay, I examine the returns to education for first, second and third generation immigrant men. Multivariate regression results indicate that the third generation with at least postsecondary education earn more than the equally educated first and second generations. However, the third generation do not have a wage premium over the second generation when they have high school education and lower. I explain the well-educated second generation's difficulty in translating their intellectual ability into productivity by their ethnic and linguistic distance from the Canadian mainstream, and by negative city-specific effects. I then suggest that immigrant assimilation policies that target the well-educated first and second generations should be designed to promote the acceptance of their human capital by the Canadian labour market.
Keywords: immigration; economics; empirical research; wage growth